PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 016 PULAU RAMBAI KECAMATAN KAMPAR TIMUR - ', Mariana; Marhadi, Hendri; ', Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by the fact that low student learning outcomes IPS. It can be seen from the IPS students with the average - average of 60. The percentage of students who achieve KKM only 45% of the 20 students, so the number of students who completed only 9 people. The purpose of this research is to improve student learning outcomes IPS Class IV Elementary School 016 East Kampar District Pulau Rambai with the implementation of cooperative learning model type STAD. Activities teachers during the learning process by using STAD cooperative learning experience penigkatan. In cycle 1 to the first meeting with the average - average 47% of the category "pretty good" after a second meeting with the average - average 56% also in the category of "good enough". After the cycle II meeting to 3 increased with the average - average 69% "good" category at the meeting to 4 with the average - average 73% of the category "good" Activities of students during the learning process with the implementation of cooperative learning model STAD increased. I cycle to the first meeting of the student activity with the average - average 50% in the classification of "high enough" to the second meeting with the average - average 57% classified as "quite high". After the cycle II meeting to 3 increased with the average - average 69% "good" category at the meeting to 4 with the average - average 73% of the category "good" Activities of students during the learning process with the implementation of cooperative learning model STAD increased. I cycle to the first meeting of the student activity with the average - average 50% in the classification of "high enough" to the second meeting with the average - average 57% classified as "quite high". After the cycle II meeting to 3 with the average - average 65% classified as "high" and at the meeting to 4 with the average - average 82 classified as "very high". During the learning process with the implementation of cooperative learning model STAD, increased student learning outcomes are seen from the results of student learning between basic score with the average - average 61 student learning outcomes in UH I with the average - average learning outcomes of 79, while the average - average learning outcomes UH students in the second cycle was 80. Key words: Learning Model STAD cooperative learning outcomes Social Sciences